Cataract surgery and the risk of developing recurrence or progression of diabetic macular edema - Mirinae Kim; Young-Gun Park; Young-Hoon Park (PLoS ONE, 2025)
Purpose To determine whether uneventful cataract surgery in patients with diabetic macular edema (DME) affects the course of the disease, and its relationship with postoperative clinical outcomes in real-world settings. Materials and Methods This retrospective cohort study included patients of center-involving DME and a prior history of periocular injection in the operative eye before cataract surgery with a follow-up of at least 6 months. Patients were assigned to active and inactive DME group according to preoperative status. Patients’ clinical outcome measurements before and after cataract surgery were compared between the groups. Cox-proportional hazards model was performed to identify risk factors of DME recurrence or progression after cataract surgery. Results The study included 153 eyes in 153 patients. No significant differences were observed in the trend of the groups’ clinical outcomes, including best-corrected visual acuity, central macular thickness and central choroidal thickness (P = .763,.872, and.127, respectively). Patients with higher HbA1c were more likely to develop recurrence or progression of DME after cataract surgery (hazard ratio = 1.407, P = .039). Conclusion The clinical outcomes following cataract surgery in patients with inactive or actively treated DME did not show significant differences at any postoperative period. Recurrence or progression of DME after cataract surgery was found to be associated with high HbA1c. Clinicians do not have to delay the cataract surgery in patients with DME who have good glycemic control and are undergoing treatment as needed.